Cross-species spill-over potential of the H9N2 bat influenza A virus - El-Shesheny, Rabeh; Franks, John; Kandeil, Ahmed; Badra, Rebecca; Turner, Jasmine; Seiler, Patrick; Marathe, Bindumadhav M.; Jeevan, Trushar; Kercher, Lisa; Hu, Meng; Sim, Yul Eum; Hui, Kenrie P. Y.; et al. (Nature communications, 2024)
In 2017, a novel influenza A virus (IAV) was isolated from an Egyptian fruit bat. In contrast to other bat influenza viruses, the virus was related to avian A(H9N2) viruses and was probably the result of a bird-to-bat transmission event. To determine the cross-species spill-over potential, we biologically characterize features of A/bat/Egypt/381OP/2017(H9N2). The virus has a pH inactivation profile and neuraminidase activity similar to those of human-adapted IAVs. Despite the virus having an avian virus–like preference for α2,3 sialic acid receptors, it is unable to replicate in male mallard ducks; however, it readily infects ex-vivo human respiratory cell cultures and replicates in the lungs of female mice. A/bat/Egypt/381OP/2017 replicates in the upper respiratory tract of experimentally-infected male ferrets featuring direct-contact and airborne transmission. These data suggest that the bat A(H9N2) virus has features associated with increased risk to humans without a shift to a preference for α2,6 sialic acid receptors. In this study, the authors report that a bat influenza A (H9N2) virus shows receptor binding features similar to avian influenza viruses, efficiently infects ex-vivo human respiratory cells and replicates in the lungs of mice and upper respiratory tract of ferrets following airborne transmission.